Modeling of the Nano-acoustic-electronic Converter on the Basis of Graphene Nanotubes - R.M. Peleshchak; I.R. Peleshchak; O.V. Kuzyk; O.O. Dan’kiv (Журнал нано- та електронної фізики)
In paper the model of the nano-acoustic-electronic converter on the basis of graphene nanotube is constructed and the amplitude-frequency characteristic is calculated. Within this model the frequency dependences of amplitude of deformation, surface concentration of electrons and electrostatic potential are established. It is established that at increase in concentration of electrons and reduction of radius of nanotube the sensitivity of the nanoconverter increases.